Tryptophan: A Unique Role in the Critically Ill - Kanova, Marcela; Kohout, Pavel (International journal of molecular sciences, 2021)
Tryptophan is an essential amino acid whose metabolites play key roles in diverse physiological processes. Due to low reserves in the body, especially under various catabolic conditions, tryptophan deficiency manifests itself rapidly, and both the serotonin and kynurenine pathways of metabolism are clinically significant in critically ill patients. In this review, we highlight these pathways as sources of serotonin and melatonin, which then regulate neurotransmission, influence circadian rhythm, cognitive functions, and the development of delirium. Kynurenines serve important signaling functions in inter-organ communication and modulate endogenous inflammation. Increased plasma kynurenine levels and kynurenine-tryptophan ratios are early indicators for the development of sepsis. They also influence the regulation of skeletal muscle mass and thereby the development of polyneuromyopathy in critically ill patients. The modulation of tryptophan metabolism could help prevent and treat age-related disease with low grade chronic inflammation as well as post intensive care syndrome in all its varied manifestations: cognitive decline (including delirium or dementia), physical impairment (catabolism, protein breakdown, loss of muscle mass and tone), and mental impairment (depression, anxiety or post-traumatic stress disorder).
Keywords: Critical Illness; deprese; post intensive care syndrome; Serotonin; kynurenin; Depression; inflammation; lidé; serotonin; melatonin; Humans; tryptofan; serotonin pathway; Kynurenine; tryptophan metabolism; kritický stav; zánět; indolamin-2,3,-dioxygenasa; sepse; polyneuromyopathy; kynurenine pathway; Delirium; Sepsis; delirium; rapamycin; sepsis; kosterní svaly; Muscle, Skeletal; Tryptophan; Inflammation; Indoleamine-Pyrrole 2,3,-Dioxygenase; Melatonin